Sexism in Elementary EFL Textbooks: Spotted in Uzbekistan - Norova, Nasiba (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The current study examines the representation of gender in four English as a Foreign Language (EFL) textbooks, Kid’s English, for elementary students produced in Uzbekistan. The study implements Fairclough's (2013) three-dimensional discourse approach: description, interpretation, and explanation for textbook analysis. The quantitative analysis of EFL textbooks unveiled an imbalance in gender representation depicting males more than females. Underrepresentation of females in the textbooks demonstrates that Kids' English EFL textbooks have a sexist ideology and stereotypical agenda. The study suggests that the sexist ideology of the textbooks perpetuates patriarchy and unfair gender societal values hindering the development of gender equality efforts in the EFL context of Uzbekistan.